Advanced die-level assembly techniques and quality analysis for phase-only liquid crystal on silicon devices. (September 2016) - Zhang, Zichen; Pivnenko, Mike; Medina-Salazar, Ivonne; You, Zheng; Chu, Daping
In this article, quality analysis of the assembled phase-only liquid crystal on silicon devices is presented based on experiences using the flexibility and scalability of die-level assembly process. The research contents mainly consist of quality control and optimisation of liquid crystal filling process and device overall quality assessment including the thickness uniformity of liquid crystal layer with post-assembly inspection. To summarise, pre-production prototype phase-only liquid crystal on silicon devices with high quality has been developed in high reproducibility using a die-level assembly process, the robust glue deposition is performed, liquid crystal filling process in isotropic phase is presented and thickness variation can be controlled in the range of λ /4.